The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/pcn5.81
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of mild behavioral impairment: A systematic review

Abstract: There are many neuroimaging studies of mild behavioral impairment (MBI), but the results have been somewhat inconsistent. Moreover, it remains unclear whether MBI is a risk factor or prodromal symptom of dementia. Therefore, a systematic review was conducted to summarize the results of neuroimaging studies of MBI and consider whether MBI is a prodromal symptom of dementia in terms of its neural correlates.A systematic review supported by a JSPS Grant-in-Aid for Scientific Research (C) was conducted using MBI n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…Of note, while widespread alterations in fronto-parietal regions were found in previous studies investigating connectivity changes related to MBI correlates (12,13,25,90), we found that the MBI subscores of affectivity, impulse dyscontrol and social inappropriateness were associated with local network properties of speci c brain regions such as the IFG and PCC. This difference could be partially attributed to the methodological differences between our graph analysis approach and the seed-based connectivity analyses performed in these studies (12,13).…”
Section: Discussioncontrasting
confidence: 66%
“…Of note, while widespread alterations in fronto-parietal regions were found in previous studies investigating connectivity changes related to MBI correlates (12,13,25,90), we found that the MBI subscores of affectivity, impulse dyscontrol and social inappropriateness were associated with local network properties of speci c brain regions such as the IFG and PCC. This difference could be partially attributed to the methodological differences between our graph analysis approach and the seed-based connectivity analyses performed in these studies (12,13).…”
Section: Discussioncontrasting
confidence: 66%
“…Findings also align with the bulk of the MBI literature comprising epidemiological or cohort studies with MBI as exposure, and outcomes of cognition, function, or risk marker. Consistently, whether in CN, MCI, or mixed dementia-free samples, or whether in clinical, community, or even online cohort studies, the data have consistently shown that selecting NPS in accordance with MBI criteria identifies a group with greater baseline risk [ 37 , 46 – 52 ], and/or greater risk for incident MCI and dementia [ 12 20 , 41 , 53 , 54 ] than the comparator groups.…”
Section: Discussionmentioning
confidence: 78%
“…Much of the MBI biomarker literature has focused on fluid biomarkers and structural (Matsuoka et al, 2023) and functional (Ghahremani, M. et al, 2023) imaging. Relatively little data have explored ligand-based PET imaging.…”
Section: Introductionmentioning
confidence: 99%